STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN SISWA MELALUI PENDEKATAN SAINTIFIK - Adya Pribadi, Reksa; Rakhmawati, Devi; Inggit Rachayu, Sri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Lack of teacher strategies in improving the ability of students in the learning process. The application of the scientific approach as a new strategy that can be used by teachers in the learning process. This study aims to improve the ability of students and make students more active in seeking their own knowledge and skills through the application of a scientific approach at SDIT Irsyadul Ibad. This study uses a qualitative method with data analysis using the Miles and Huberman model. Data collection techniques include data reduction and presentation, as well as drawing conclusions. The data collection instruments are observation, interview, and documentation techniques. Based on the research that has been done, it shows that the teacher in the learning process in class 5A Tariq Bin Ziyad has applied a scientific approach which includes 5M activities of asking, observing, reasoning, gathering information and communicating. The implementation of the scientific approach makes students more active in learning, increasing self-confidence, asking questions and communicating. Produce students with character so that they are able to seek their own knowledge and skills.